Impact of Choline Chloride and Organic Acid-Based Deep Eutectic Solvents on the Extraction of Bioactive Compounds from Grape Pomace - Thao Thi Thanh Nguyen; Viet Bao Nguyen; Tuyen Chan Kha; Hoang Van Chuyen (Journal of Technical Education Science, 2024)
The objective of this study was to determine the impact of the extraction conditions on the extraction yield of bioactive compounds from grape pomace using choline chloride and organic acid-based deep eutectic solvents (DES). Three different types of DES were used, including choline chloride-lactic acid, choline chloride-malic acid, and choline chloride-citric acid. The effect of the ratios of hydrogen bond acceptor to hydrogen bond donor (2:1, 1:1, 1:2, 1:3), the water addition in the DES (10–35%), the solid-to-solvent ratio (1/15–1/30 (w/w)), and extraction time (1.5–4 hours) on extraction were also investigated. The results showed that the highest total extraction yield was obtained using a DES based on choline chloride and lactic acid with a ratio of 1:2, 20% water, a solid-to-solvent ratio of 1/25 (w/w), and an extraction time of 2.0 hours. Under the best extraction conditions, the total phenolic content (TPC), total saponin content (TSC), and proanthocyanidin content (PAC) of the extract from grape pomace were found to be 42.53 ± 0.52 mg GAE/g DW, 101.43 ± 1.22 mg AE/g DW, and 17.11 ± 0.18 mg CE/g DW, respectively.